2020
DOI: 10.1038/s42254-020-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical hydrodynamics of droplets out of equilibrium

Abstract: Droplets abound in nature and technology. In general, they are multicomponent, and, when out of equilibrium, with gradients in concentration, implying flow and mass transport. Moreover, phase transitions can occur, with either evaporation, solidification, dissolution, or nucleation of a new phase. The droplets and their surrounding liquid can be binary, ternary, or contain even more components, and with several even in different phases. In the last two decades the rapid advances in experimental and numerical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
237
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(241 citation statements)
references
References 236 publications
(331 reference statements)
4
237
0
Order By: Relevance
“…Clearly, buoyancy will also play a prominent role in the interfacial breakup in other turbulent flows, such as Bénard-Marangoni convection, and horizontal and vertical convection. All these phenomena add to the richness of physico-chemical hydrodynamics of droplets far from equilibrium (Lohse & Zhang 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, buoyancy will also play a prominent role in the interfacial breakup in other turbulent flows, such as Bénard-Marangoni convection, and horizontal and vertical convection. All these phenomena add to the richness of physico-chemical hydrodynamics of droplets far from equilibrium (Lohse & Zhang 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies on multicomponent droplets have revealed attractive physical phenomena (Lohse & Zhang 2020) induced by the preferential evaporation of individual components or mediated by external vapour sources, e.g. the occurrence of density-driven flows (Edwards et al 2018;Li et al 2019), phase segregation/separation (Li et al 2018;Li et al 2020;Mao et al 2020), the transient Marangoni flow and solutal effects (Christy, Hamamoto & Sefiane 2011), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation can be overcome in a bottom-up approach such as solvent exchange (Lou et al 2000;, 2020Zhang et al 2015), where a large number of micro-and nanodroplets are generated by nucleation out of an oversaturated solution. This method, also called nanoprecipitation or solvent shifting (Fessi et al 1989;Galindo-Rodriguez et al 2004;Aubry et al 2009;Lepeltier, Bourgaux & Couvreur 2014;Hajian & Hardt 2015), though commonly used, is much less well understood.…”
Section: Introductionmentioning
confidence: 99%